Analisis Mutu Pindang Ikan Tongkol (Euthynnus affinis) dengan Teknik Pengolahan Oven Steam - Rezaldi Hidayat; Maimun Maimun; Sukarno Sukarno (Jurnal FishtecH, 2020)
Fish has a significant contribution in fulfilling the protein source of Indonesian people. The target in 2019 reached 54.49% in efforts to increase food consumption in all layers by providing high quality Indonesian marine products. There are high-economic fish species, namely tuna, skipjack, mackerel, bloating, flying were the raw material in the processing of boiled fish. Pemindangan was a processing technique and preservation, the purpose of this study is to find out the quality of the steam oven produced by distinguishing the cooking time, by knowing the final product sensory test and proximate test, the final product sensory test shows no difference in each cooking whereas the odor, taste, texture parameters are Significant differences in cooking and proximate testing of the three cooking there is no significant difference (p>0.05) to the quality produced, but the product preferred by consumers was a product with 3 hours of cooking, so the cooking recommended on the use of an oven this steam was 3 hours cooking.